2019
DOI: 10.1007/s12034-019-1740-5
|View full text |Cite
|
Sign up to set email alerts
|

Dextran from Leuconostoc mesenteroides-doped ammonium salt-based green polymer electrolyte

Abstract: Biopolymer electrolytes based on dextran from Leuconostoc mesenteroides doped with ammonium nitrate (NH 4 NO 3) are synthesized via a solution cast method. Fourier transform infrared analysis is used to determine the complexation between cation from the salt with functional groups of dextran. The ionic conductivity of undoped dextran film at room temperature is identified as (8.24 ± 0.31) × 10 −11 S cm −1. A conductivity of (3.00 ± 1.60) × 10 −5 S cm −1 is achieved with the inclusion of 20 wt% NH 4 NO 3 to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 45 publications
(34 reference statements)
3
29
0
Order By: Relevance
“…Clearly, ε ′ and ε ″ decline gradually until they attain the lowest value when there is a rise in the frequency and become nearly constant when frequencies are extremely high. The electrode polarization effect is responsible for the higher values acquired for each parameter in the low-frequency region [ 91 , 92 ]. The following relation shows the strong association between dielectric constant ( ε ′) and density number of charge carriers ( n ); where U represents the dissociation energy, T represents the absolute temperature, n 0 represents pre-exponential constant, and k B represents the Boltzmann constant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, ε ′ and ε ″ decline gradually until they attain the lowest value when there is a rise in the frequency and become nearly constant when frequencies are extremely high. The electrode polarization effect is responsible for the higher values acquired for each parameter in the low-frequency region [ 91 , 92 ]. The following relation shows the strong association between dielectric constant ( ε ′) and density number of charge carriers ( n ); where U represents the dissociation energy, T represents the absolute temperature, n 0 represents pre-exponential constant, and k B represents the Boltzmann constant.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the conductivity and the relaxation associated with conductivity in ionic conductors as well as polymers can be conveniently studied with the help of the electric modulus curves [ 8 ]. The issues that impeded the complete analysis and detailed permittivity relaxation including electrode nature, space charge mechanism and conduction impacts can be addressed [ 55 , 92 , 98 , 99 ]. The formulas given below allow the calculation of the real and imaginary parts of complex electric modulus (M*) by inserting the values of the real ( Z r ) and imaginary ( Z i ) parts of complex impedance (Z*) [ 55 , 82 ]: where angular frequency is denoted by ω , capacitance of dielectric cell without the sample is denoted by C o , Z r denotes the real part of impedance and Z i denotes the imaginary part of the impedance.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 provides insight into the PVA:CS blending system, indicating that there is no observable peak at 2θ =18.6 • , which is the characteristic peak that appears for the pure PVA polymer. It is also observed that the hollow intensity decreases, and the broadening of line-width upon blending can be attributed to amorphous development [30].The XRD pattern for the PVA:CS blend electrolytes doped with various quantities of NH 4 I is exhibited in Figure 3. Obviously, it can be seen that as NH 4 I salt is increased up to 40 wt.% in the PVA:CS system, the hollow intensity substantially reduces and is accompanied by peak broadening.…”
Section: Structural Studymentioning
confidence: 95%
“…The impedance results are in strong agreement with the XRD results. The sharp peaks that correspond to the pure NH4I salt obviously appear to be shifted as a consequence of the ion association that lowers conductivity [30]. All these suggest that it is straightforward to detect ion association within electrolyte polymers using EIS.…”
Section: Impedance and Ac Conductivity Studymentioning
confidence: 96%
“…With these interesting characteristics, a polymer electrolyte can be made out of it [ 7 ]. The inclusion of 20 wt.% ammonium nitrate (NH 4 NO 3 ) into a DX host increased the conductivity from (8.24 ± 0.31) × 10 −11 to (3.00 ± 1.60) × 10 −5 S/cm [ 8 ]. A DC ionic conductivity of (1.67 ± 0.36) × 10 −6 S/cm was acquired with 20 wt.% ammonium bromide (NH 4 Br) in the DX matrix [ 9 ].…”
Section: Introductionmentioning
confidence: 99%